Pore-Scale Investigations of Rock and Fluid Microstructure and Fluid Displacement Processes in Geological Porous Media - Taufiqurrahman (Curtin University, 2018)
This study evaluates the super critical carbon dioxide trapping capacity of oil-wet formations at reservoir conditions via x-ray micro-computed tomography. The CO2 clusters and their morphologies were analysed statistically, and it is clear that residual saturations are approximately halved in oil-wet rock, while cluster morphology also changes into flatter clusters.